The ethical and legal issues of organoid biobanks - Katsila, Michailina (Bioethica, 2023)
Organoid technology has been of interest to the academic and scientific community. In particular, the storage of organoids in biobanks has introduced research opportunities in the fields of biomedicine and biotechnology. Whilst biobanks contribute to the scientific investigation of the physiology and function of organoids, they also face challenging ethical and legal issues. This article aims to analyse the multidimensional ethical and legal issues involved in the operation of organoid biobanks and to propose measures to be considered at varying stages in order to ensure, both ethically and legally, their scientific impact. The issues address informed consent and the privacy of cell donors, the commercialisation of organoids and the possible closure of the biobank. Current guidelines and regulatory frameworks applicable to organoids and biobanks are also addressed. It is concluded that, despite the considerable ethical and legal challenges raised by the use of organoid biobanks, there is a need to ensure that the biobanks are operational in order to exploit the potential benefits of organoids. To this regard, it is recommended to establish procedures, develop protocols for assurance and quality. From this standpoint, organoid biobanks can contribute to maximising the biomedical and welfare benefits of organoid research as well as contributing to the future regulation of organoid technology.